An experimental and numerical investigation on hydrodynamic characteristics of the bow thruster. (1st August 2020) - Yukun, Feng; Zuogang, Chen; Yi, Dai; Zheng, Zhang; Ping, Wang
Abstract: While maneuvering or positioning in different situations, the hull, the angle of the inlet current, and the tunnel opening fairing onto the hull have serious impacts on the performance of the bow thruster. The co-operation of multiple bow thrusters affects each other in the hydrodynamic performance. In this study, we report a thorough investigation of the hydrodynamic performance of the bow thruster combining experimental and numerical methods. The influence of the hull, the inflow angle, and the fillet radius of the tunnel opening is considered. The interaction between multiple bow thrusters is also studied. Open water tests and single bow thruster tests with the hull at eight different inflow angles were performed. Numerical simulations under the same condition were performed using the u-RANS method, and the accuracy of numerical results is verified by comparing with experimental data. Then, the flow field details of the single bow thruster condition were extracted. By analyzing the velocity distribution in the tunnel, the coupling influence of the hull and the inflow angle can be studied. Moreover, numerical simulations were performed for four hull models with different fillet radii for the tunnel opening. The influence of the opening fairing is analyzed by comparing numerical results and detailed flow fields. Finally, the co-operation of two bow thrusters is simulated, and the interaction between three bow thrusters is investigated. The results show that the joint influence will lead to a large-scale, asymmetric reversed flow zone at the tunnel opening. The reversed flow zone changes with the inflow angle and leads to a great difference in pressure distribution for different blades of the propeller. The opening fairing of the tunnel can improve the uniformity of the flow field in the tunnel, restrain the asymmetric pressure distribution on the propeller, and raise the efficiency of bow thruster. In addition, during co-operation, the induced flow direction of the propeller has a significant influence on the performance of the bow thruster. The upstream bow thruster can slightly improve the efficiency of the downstream bow thruster. Highlights: Experimental and high-accuracy numerical method is applied to investigate the hydrodynamic performance of the bow thruster. The coupling effect of the hull, inflow direction and propeller induced flow is studied by analyzing detailed flow field. The effect of the faring of the tunnel opening is analyzed. Numerical simulations with different fillet radii is conducted. The co-operation of multiple bow-thrusters is carried out. The interaction between multiple bow thrusters is investigated.